Listen listen listen: an online listening tool / Roslina Mohd Jani … [et al.] - Mohd Jani, Roslina; Maktiar Singh, Kuldip Kaur; Vijayarajoo, Angeline Ranjethamoney; Martin, Caroline; Gan, Kiat Chien (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
This paper presents an innovative product which is aimed at improving the listening component of the ELC 120 code (English Language Proficiency Course for Part 1, Diploma Level students in UiTM, Malaysia). This is a new code, having just begun, one semester ago, since July, 2013. Listening, one of the four core skills in any language syllabus is important. This is especially so, in the local context. However, the listening component of ELC 120, goes beyond that, to foster a love for, and enjoyment of, the language. Tasks include, enrichment of the language in simple terms, while introducing open ended literary responses to the genre of short stories. The responses required of students include comments on the literary devices used, such as the plot, character, theme/s, values and providing alternative ways of ending the story. Thus, the tasks also invite and encourage the creativity of students to think out of the box, while developing the aesthetic responses of students. Currently, the short stories used are taken from International settings with foreign contexts, vocabulary and pronunciation. Hence, the project members have written their own, and original short stories, with a Malaysian context, in terms of theme/s, vocabulary and pronunciation. Considering the target student population, of year one Diploma level students, the project members felt that a more local context was needed, with a Malaysian identity.